Fabrication of micro/nanostructured α-Fe2O3 hollow spheres: effect of electric field on the morphological, magnetic and photocatalytic properties. Issue 70 (12th July 2016) - Kant, Rich; Kumar, Neetesh; Dutta, Viresh
Abstract : Continuous fabrication of α-Fe2 O3 hollow spheres with sponge like morphology using an electric field assisted (by applying DC voltage) continuous spray pyrolysis (CoSP) technique. Abstract : In this paper, we reported the continuous fabrication of α-Fe2 O3 hollow spheres with sponge like morphology using an electric field assisted (by applying DC voltage) continuous spray pyrolysis technique. The effect of applied voltage on the morphological, magnetic and photocatalytic properties is systematically studied. The samples prepared under an electric field have shown enhanced magnetic and photocatalytic properties compared to the samples prepared without an electric field (0 kV). It is observed that the sample fabricated at an applied voltage of 2 kV has a remarkably high coercivity ( H C ) of ∼4.5 kOe and manifested the maximum degradation efficiency of 98% and 95% under visible light for methylene blue and rhodamine B dye, respectively owing to its sponge like morphology, enhanced surface area and pore volume. These α-Fe2 O3 samples have potential applications in large memory devices, permanent magnets and efficient adsorbent materials for the removal of organic pollutants from water.